The Use of E-Learning Using Web-Based Management Introduction In Pamulang University - Ni’mah, Ni’mah; Khaerudin, Khaerudin; Kusumawardani, Dwi (International Journal for Educational and Vocational Studies, 2020)
Web-based e-learning in management introductory courses at Pamulang University, this study discusses studying e-learning in subjects at Pamulang University specifically on management introductory courses. This research was conducted at Pamulang University. This research was conducted in March 2020 until July 2020. The research method uses qualitative methods with primary data or secondary data. The results of this study indicate that the use of e-learning at Pamulang University has provided benefits for system improvement and for improving the quality of comfort. And e-learning learning has been implemented well by Pamulang University or more focused on management study programs. Because e-learning has become a mandatory part, Pamulang University continues to improve so that its utilization continues to improve. At least some of the things that are unique from this research are the University of Pamulang using e-learning as a whole. All subjects must be scheduled to represent lectures conducted face-to-face. This supports the un pam students to have a closeness with technology.